Prevalence, predictors, and management of advanced HIV disease among individuals initiating ART in Senegal, West Africa - Benzekri, Noelle A. (BMC Infect Dis, 2019)
BACKGROUND: The WHO guidelines for the management of advanced HIV disease recommend a package of care consisting of rapid initiation of antiretroviral therapy (ART), enhanced screening and diagnosis of tuberculosis (TB) and cryptococcal meningitis, co-trimoxazole prophylaxis, isoniazid preventive therapy (IPT), fluconazole pre-emptive therapy, and adherence support. The goals of this study were to determine the prevalence of advanced HIV disease among individuals initiating ART in Senegal, to identify predictors of advanced disease, and to evaluate adherence to the WHO guidelines. METHODS: This study was conducted among HIV-positive individuals initiating ART in Dakar and Ziguinchor, Senegal. Clinical evaluations, laboratory analyses, questionnaires and chart review were conducted. Logistic regression was used to identify predictors of advanced disease. RESULTS: A total of 198 subjects were enrolled; 70% were female. The majority of subjects (71%) had advanced HIV disease, defined by the WHO as a CD4 count < 200 cells/mm(3) or clinical stage 3 or 4. The median CD4 count was 185 cells/mm(3). The strongest predictors of advanced disease were age ≥ 35 (OR 5.80, 95%CI 2.35–14.30) and having sought care from a traditional healer (OR 3.86, 95%CI 1.17–12.78). Approximately one third of subjects initiated ART within 7 days of diagnosis. Co-trimoxazole prophylaxis was provided to 65% of subjects with CD4 counts ≤350 cells/mm(3) or stage 3 or 4 disease. TB symptom screening was available for 166 subjects; 54% reported TB symptoms. Among those with TB symptoms, 39% underwent diagnostic evaluation. Among those eligible for IPT, one subject received isoniazid. No subjects underwent CrAg screening or received fluconazole to prevent cryptococcal meningitis. CONCLUSIONS: This is the first study to report an association between seeking care from a traditional healer and presentation with WHO defined advanced disease in sub-Saharan Africa. Given the widespread use of traditional healers in sub-Saharan Africa, future studies to further explore this finding are indicated. Although the majority of individuals in this study presented with advanced disease and warranted management according to WHO guidelines, there were numerous missed opportunities to prevent HIV-associated morbidity and mortality. Programmatic evaluation is needed to identify barriers to implementation of the WHO guidelines and enhanced funding for operational research is indicated.